2012
DOI: 10.4414/smw.2012.13671
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and quality of life of elderly patients after intensive care

Abstract: Ageing of the world's population raises important questions about the utilisation of the health care system. It is not clear how much should be invested in the last years of life whereas the costs are known to increase in parallel. Since intensive care units (ICU) are costly with highly specialised personnel, it seems of paramount importance that they would be used efficiently. Indeed, in the present context of predicted shortage of physicians in Switzerland, society and politics will need evidence that the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 71 publications
2
23
1
5
Order By: Relevance
“…After facing severe illness, older patients are likely to assign higher scores to their quality of life. (14,15,17) A study with elderly individuals aged 80 years or older also showed that quality of life was preserved in the majority of patients after ICU admission. (18) …”
Section: Discussionmentioning
confidence: 99%
“…After facing severe illness, older patients are likely to assign higher scores to their quality of life. (14,15,17) A study with elderly individuals aged 80 years or older also showed that quality of life was preserved in the majority of patients after ICU admission. (18) …”
Section: Discussionmentioning
confidence: 99%
“…The issues regarding end-of-life care for elderly patients even in the ICU are currently being raised with greater frequency [7, 8]. We therefore wish to highlight the issue of end-of-life care and decision-making in the ICU focusing on NDT.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, a avaliação inicial antes do internamento na UCI foi realizada, o que é crucial quando se estuda o impacto da doença crítica (Oeyen, et al, 2010). Adicionalmente, levando em consideração que a QVRS pode diminuir ao longo do tempo (Hopman et al, 2014) e há diferentes pontuações de QV em pessoas com a mesma idade cronológica (Conti, Merlani, & Ricou, 2012), entende-se que faz sentido que os idosos voltem a um nível semelhante ao de antes do internamento, a fim de saber se as alterações refletem o impacto da doença crítica ou um nível baixo antes dos cuidados intensivos.…”
Section: Sintomas Depressivos Em Idosos Que Estiveram Internados Numaunclassified
“…Este fenómeno origina a necessidade da existência de mais recursos em saúde, incluindo os cuidados intensivos (Conti, Merlani, & Ricou, 2012), onde os idosos representam entre 30% até quase 50% do total da população da UCI na Europa (Castelló, Cabello, Goixart, Llanes, & Rodríguez-Pozo, 2008;López-Soto, 2005). Neste contexto, a adequação do sistema de saúde à população idosa assume-se como um importante desafio (Chamie, 2010).…”
Section: Introductionunclassified
See 1 more Smart Citation